PERSEPSI KELUARGA PETANI TERHADAP PENDIDIKAN FORMAL ANAK (Studi Tentang Keluarga Anak Putus Sekolah di Desa Baturijal Hulu Kecamatan Peranap Kabupaten Indragiri Hulu) - Harmayani "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Education is very important in the era of globalization, and the school is a container of children's learning from the level of primary school education or elementary, junior high, high school and to university. Primary education is compulsory education nine years, but until now there are still many children who drop out of school in the village of Baturijal Hulu subdistrict Peranap Indragiri Hulu starting from elementary, junior high and high school that causes by various factors such as economic factors factor of failing a grade, own volition factor (lazy) environmental factors and factor the lack of motivation of the family. This research was conducted in the village of Upper Baturijal Peranap District of Indragiri Hulu, this research specifically on parents of school dropouts and children who drop out of school in the academic year 2015/2016 are still in the village of Upper Baturijal with the objective to analyze the perception of parents for children's education and children's activities after dropping out of school. The theory used is the theory of perception and motivation theory. This research is a qualitative descriptive study using purposive sampling methods, data collection by interview, observation and documentation. The number of informants in this study were 17 people consisting of seven parents of children who drop out of school, 7 dropouts and 3 people informant supporters. The results showed that children who drop out of school more due to the child's place of environmental factors. Parents have the view that it was very important pendidika, with their education will increase knowledge and insight for their children. But not all parents have a good pandagan to education, there are also parents who think that education is not important and only spend money. Activities undertaken after dropping out of school children visits from elementary children spend more time to play, further visits of school children from junior and senior high school children prefer to work to help their parents.Keywords: Perception, Dropouts, Activities